Tata Kelola Media Sosial Bagi Penguatan Sistem Pemerintahan Desa Tanjungsari Kabupaten Serang - Wahyiah, Ita Rosita; Lestari, Elly Rohayani; Bate’e, Welni Desrinayanti; Ilham, Rifky; Arianto, Bambang (TAAWUN, 2023)
The use of social media has created various dependencies in all sectors of life, especially for strengthening the government system. This is because social media can be the most important information channel for strengthening the rural governance system. However, the main obstacle faced in using social media is the competence and knowledge possessed by village government officials. This service aims to enable village government staff to utilize social media to strengthen the government system, especially as an information channel. In community service in Tanjungsari Village, Serang Regency which was held on 28th July 2023, assistance was provided regarding social media management. The method used in this service is participatory counseling and mentoring. This assistance provided various knowledge about social media governance techniques, starting from admin management, creative content, copywriting, and viral management. The success of this activity can be seen in Village Government officials who can manage social media as village information channels and create creative content. From the results of this activity, it is known that social media governance can strengthen the government system in Tanjungsari Village, Serang Regency.